Analisis Determinan Kinerja Sistem Informasi Akuntansi pada Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Jember - Imelda Rizky Aulia; Berlina Yudha Pratiwi (Politeknik Negeri Jember, 2022)
This study aims to analyze the factors that influence the performance of the Accounting Information System (AIS) at the Regional Financial and Asset Management Agency of Jember Regency. This study uses a causal associative method with a quantitative approach. The population in this study were all employees who worked at BPKAD Jember Regency as many as 69 employees. The sampling technique used purposive sampling technique so that the sample in this study were 33 employees. This study uses a IBM SPSS application for analysis data. The results of data processing show that user participation in system development and personal technical skills have a significant positive effect on the performance of accounting information systems, while education and training programs and top management support have no significant positive effect on accounting information system performance.